Further studies to evaluate methods of leucoreduction to prevent alloimmune platelet refractoriness and induce tolerance in a dog platelet transfusion model. Issue 1 (23rd March 2016) - Slichter, S. J.; Abrams, K.; Bailey, S. Lawrence; Pellham, E.; Gettinger, I.; Christoffel, T.; Gaur, L.; Latchman, Y.; Nelson, K.; Bolgiano, D.
Abstract : Objectives: Three leucoreduction filters were evaluated – when used alone or combined with centrifuge leucoreduction (C‐LR) – to prevent alloimmune platelet refractoriness in a dog platelet transfusion model. Materials and Methods: Donor platelet‐rich plasma (PRP) or buffy coat (BC) platelets were either filter leucoreduced (F‐LR) or F‐LR/C‐LR, 51 Cr radiolabelled and transfused. Weekly transfusions were given for up to 8 weeks or until platelet refractoriness. Recipients who accepted treated transfusions were then given non‐leucoreduced (non‐LR) platelets to determine whether donor‐specific tolerance had been induced. Results: Acceptance of F‐LR PRP transfusions ranged from 29% to 66%. F‐LR/C‐LR transfusions prepared from PRP were accepted by 92%, from BC by 63% and from pooled PRP by 75% of recipients (p=NS); overall acceptance rate of F‐LR/C‐LR transfusions was 83%. Tolerance to subsequent non‐LR transfusions occurred in 45% of the F‐LR‐/C‐LR‐accepting recipients unrelated to DR‐B compatibility between donors and recipients ( P = 0·18). Conclusion: In a dog platelet transfusion model, acceptance of donor platelets required combining F‐LR with C‐LR as apparently each process removes different immunizing WBCs.